2004
DOI: 10.1002/joc.1084
|View full text |Cite
|
Sign up to set email alerts
|

Middle East climate simulation and dominant precipitation processes

Abstract: The ability of both the ECMWF-TOGA analyses and regional model RegCM2 to simulate the climate of the Middle East is examined. The climate of the region displays high spatial, seasonal and interannual variability, providing a strong test of a climate model's abilities. The higher resolution of RegCM2, compared with the ECMWF analyses, allows it to capture the spatial variability of temperature and precipitation better despite model biases being present. Both RegCM2 and the analyses have a cold bias, exacerbated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 41 publications
(38 reference statements)
4
99
0
Order By: Relevance
“…The low pressure zone in the northern Arabian Peninsula is also captured well by the models, therefore the pressure gradient in the models are quite well, compared with the observed SLP data. The subsidence motion of the Hadley cell during the dry season over the Peninsula, which suppresses convection in the region, may contribute towards this high pressure zone (Evans et al ., 2004).…”
Section: Dry Season Mean Sea Level Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…The low pressure zone in the northern Arabian Peninsula is also captured well by the models, therefore the pressure gradient in the models are quite well, compared with the observed SLP data. The subsidence motion of the Hadley cell during the dry season over the Peninsula, which suppresses convection in the region, may contribute towards this high pressure zone (Evans et al ., 2004).…”
Section: Dry Season Mean Sea Level Pressurementioning
confidence: 99%
“…The north-eastern side of the Peninsula is bordered by the Arabian Gulf; on the western side the Red Sea is located, whereas the southeastern side is bordered by the Arabian Sea. The Red Sea and the Arabian Gulf are the main sources of water vapour, given the descending motion within the Hadley cell in the region (Evans et al ., 2004). The Sudan low, Mediterranean flow, Indian monsoon and position of the Intertropical Convergence Zone (ITCZ) all control the development of rainfall systems in this region (Atlas, 1984;Walters and Sjoberg, 1988;Zekai and Khalid, 2002;Chakraborty et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in the Middle East, which has a complex climate affected by both tropical and mid-latitude processes (for example Evans, 2004). Previous studies of this region have not explicitly considered the connections between variability on different timescales, instead focusing either on daily variability or on interannual and longer timescales.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they found that the monthly and annual mean frequencies of rain events were satisfactorily reproduced by the model. Evans et al (2004) and Evans (2009) evaluated RCM performance in the Middle East using monthly, annual and seasonal totals of temperature and precipitation. As in Evans et al (2005), the model performance was evaluated against observations using several statistics, including the bias, RMSE and the modified coefficient of efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…As in Evans et al (2005), the model performance was evaluated against observations using several statistics, including the bias, RMSE and the modified coefficient of efficiency. The RegCM2 RCM which was used in Evans et al (2004) was able to capture the spatial variability of temperature and precipitation better than the European Centre for Medium-Range Weather Forecasts-Tropical Ocean and Global Atmosphere (ECMWF-TOGA) project analyses despite model biases being present. Further, the RCM, based on MM5, used in Evans (2009) showed that the model was able to simulate the precipitation well for most of the domain, while displaying a negative bias in temperature throughout the year.…”
Section: Introductionmentioning
confidence: 99%